PSYCHOLOGICAL ASPECTS OF NON-OBSERVANCE OF WORK SAFETY REGULATIONS - Brizga, Dace; Pēks, Ludis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Non-observance of work safety regulations contribute to the worsening of employees’ health condition, development of occupational diseases and the increase of the possibility of accidents. Accidents happen because they have definite causes – the attitude of employers and employees towards work safety. The aim of this study was to research the psychological aspects of non-observance of work safety regulations from the work safety specialists’ point of view. The methodology of research – studies of publications pertaining to the research theme, unstructured observations, analysis of the essays written by work safety specialists about the attitude towards work safety, motivation to observe its regulations and ignoring the regulations. The text analysis was carried out using the software programme Weft QDA.